Russo-Ukraine War: Drawing a Parallel with the Second World War and Cold War - William Abiodun Duyile; Olayinka Olabimpe Ojo; Soboyejo A. Oludemi; Gabriel G. Jegede (Polit Journal Scientific Journal of Politics, 2022)
The paper drew parallels between the Russo- Ukraine war and the Second World War and Cold War. A contextual between these events and eras were described in the study. The similarities were pointed out, a conjecture between the eras was reviewed, and a comparison of NATO and Russia’s National Interests were studied side by side as it concerns the nations border states with Russia. The study relied on documentary data. The documentary data were sourced from government annual departmental reports, newspapers and correspondence. The secondary sources used were subjected to internal and external criticism for authentication, and then to textual and contextual analyses. The study found that the Russo- Ukraine war was a proxy war. The paper proved that a parallel between the events under study can indeed be drawn. A core contribution of this study is the correlation between the eras and the similarities of both periods The study proves that Russia has a Nuclear edge over NATO.